THE WORLD PRODUCTION OF TANTALUM (REVIEW) - D. K. Omarova (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
The article presents the characteristics of the tantalum, one of the rare metals which is used in an aviationspace technology, motor electronics, and medicine and. communications electronics. The view of the main world tantalum productions has been showed in the article. The production of tantalum in the East Kazakhstan is one of the largest in the world, where the new technology of high capacity tantalum powder has been opened.